Nutrition Education, Physical Activity and Dietary Habits in Diabetes Mellitus Patients - Nuryani, Nuryani; Usman, Wiwin I; Maesarah, Maesarah (Universitas Airlangga, 2023)
The prevalence of Type 2 Diabetes Mellitus (T2DM) in Indonesian population aged 15 years increase based on a doctor's diagnosis, where DKI Jakarta is the province with highest prevalence of T2DM. Gorontalo Province itself experienced an increase prevalence of T2DM compared to Riskesdas 2013, the rose from 6.9%to 8.5%. This study aims to observe the effect of nutrition education on knowledge, physical activity and eating habits of Diabetes mellitus patients participating in Posbindu at Monano Health Center. This study uses a quantitative method with an analytical survey with a quasi-experimental approach.The sample of the study were diabetes mellitus patients who were participate in Posbindu. Using the total sampling technique where the population was sampled as many as 74 people then categorized 2 groups, intervention group and control group. Based on the results of bivariate analysis, obtained p value > α (α = 0.05) in the category of physical activity with test results showing p value = 0.271 > 0.05. The same thing also happened to carbohydrate intake with p value = 0.088 > 0.05. For knowledge and eating habits with fiber and protein intake, p < 0,05 was obtained. In conclusion, knowledge, eating habits with fiber and protein intake affect the provision of nutrition education to diabetes mellitus patients participating in Posbindu in the work area of Monano Health Center.